Nanocontainers Against Biofouling and Corrosion Degradation of Materials: A Short Review With Prospects - Kordas, George (Frontiers in Nanotechnology, 2022)
We recently developed nanocontainers for self-healing coatings with controlled corrosion inhibitors, energy storage, cement crack repair, and antifouling metal protection. We incorporated these nanocontainers into the materials in small quantities (e.g., 5−10 wt. % in paints) but gave anticorrosion protection results incomparably more than the traditional methods that exist today. Furthermore, the resulting new materials exhibited multifunctionality, such as self-healing, antibacterial, and antimicrobial. The primary purpose of this review of our work is to summarize this scattered research reported in many strewn publications designed to allow the reader to understand the possibilities offered by these new forms of nanotechnology and better show nanocontainers' prospects.